Redescription of Hypsiboas semiguttatus, with the description of a new species of the Hypsiboas pulchellus group - Garcia, Paulo C. A.; Faivovich, Julián [UNESP]; Haddad, Célio F. B. [UNESP] (My University, 2007)
We redescribe Hypsiboas semiguttatus (Lutz, 1925) and describe its tadpole and vocalization. We also describe a new species, previously confused with H. semiguttatus from Misiones, Argentina, and potentially from Brazil. This new species differs from H. semiguttatus in being more robust, having a tadpole with complete marginal papulation (no anterior gap), and a labial tooth row formula of 3/5. We discuss the status of populations previously assigned to H. semiguttatus and discuss the relationships of the new species within the Hypsiboas pulchellus group. © 2007 by the American Society of Ichthyologists and Herpetologists.
Keywords: dentition; frog; juvenile; morphology; new species; taxonomy; vocalization; Argentina; Brazil; Misiones [Argentina]; South America